Fabulous origami boxes - Fuse, Tomoko (Japan Publications Trading Co. Distributor, Kodansha America through Oxford University Press, 1998)
Boxes are one of the most popular formats of the age-old papercraft of origami. Fabulous Origami Boxes includes designs for nesting boxes, simple triangle and square boxes and more complex hexagonal and octagonal boxes. Detailed illustrations provide step-by-step instructions on the correct way to crease and fold origami paper. Many of the designs are made of one sheet of paper, but some combine individual units with intriguing results. Both practical and lovely, these boxes can be used for gift-giving, storing trinkets, or simply for display.